British and American norms in the Trinidadian English lexicon. Issue 1 (13th November 2022) - Wilson, Guyanne
Abstract: Previous work on norm orientations in the Caribbean Englishes has focussed largely on phonological norms, such as accents, and, to a lesser extent, grammatical norm orientation. Outside of the publication of dictionaries, however, lexical norms and their spread have received little attention. This paper examines lexical norm orientations in Trinidadian English, presenting the results of a corpus‐based study and survey study of the lexical preferences of speakers of Trinidadian English. The findings suggest that while there is evidence of American influence on Trinidadian lexicon, British variants persist. Indeed, British and American variants often coexist, albeit with different connotations in Trinidadian English. From a methodological standpoint, this paper demonstrates the benefits of using a mixed‐methods approach in looking at norms, particularly with regard to lexicon.